1998
DOI: 10.1590/s0066-782x1998000600006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia angiográfica do sistema venoso coronário. Aplicações em eletrofisiologia clínica

Abstract: Purpose -To study the angiographic anatomy of human coronary veins and the possibility of epicardial venous mapping through microelectrode catheters.Methods -We evaluated 30 patients with sustained ventricular tachycardia using a catheter which provided occlusion of the coronary sinus ostium during venous angiography. They were 25 males, 5 females, ages ranging from 24 to 76 years (mean=52.7). The veins were studied according to their number, caliber and distribution in the anterior and posterior wall of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The mean calibers of the GCV found in our study at the interventricular sulcus and at the distal segment (3.73 mm and 5.3 mm, respectively), are consistent with the majority of the reports from studies in humans [ 4 , 9 , 16 , 21 , 22 ] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The mean calibers of the GCV found in our study at the interventricular sulcus and at the distal segment (3.73 mm and 5.3 mm, respectively), are consistent with the majority of the reports from studies in humans [ 4 , 9 , 16 , 21 , 22 ] .…”
Section: Discussionsupporting
confidence: 92%
“…The venous communication found between the GCV and the MCV at the heart apex (49%) in our study, is considerably more numerous than those reported in humans indicating ranges between 15-34% [ 5 , 8 , 9 , 11 , 14 , 16 ] . Melo et al [ 4 ] , in a study conducted in humans, reported venous communication of these veins in 90% of the cases, although they do not discriminate where these venous communication occurred. This morphological characteristic has been considered as protective because in certain pathophysiologic conditions allow to attenuate or prolong the history of the cardiovascular disease by providing alternative routes for venous drainage [ 8 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant increase in interest in the morphology of coronary veins and their valves occurred in the 1980s after the development of new treatment modalities in invasive cardiology and cardiac surgery via cannulation of the coronary veins, particularly the coronary sinus. The presence of valves in the small cardiac veins and absence of the valves in the Thebesian veins was confirmed by a series of studies conducted in the 1980s by Lüdinghausen and coworkers, who studied these vessels with the combination of injections and histological techniques (von Lüdinghausen, , , ; von Lüdinghausen, Ohmachi, Besch & Mettenleiter, ), and the work of other authors (Tschabitscher, ; Rosinia & Low ; Melo et al, ; Cendrowska‐Pinkosz & Urbanowicz, ; Gerber et al, ; Kozlowski et al, ; Ortale, Gabriel, Iost & Marquez, ; Ho, Sanchez‐Quintana & Becker, ). All authors, however, devoted their studies to the morphology of the central region of the venous bed of the heart, thus its outermost parts (including the intramyocardial segments) were neglected.…”
Section: Introductionmentioning
confidence: 79%